1978
DOI: 10.1002/hlca.19780610207
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Addition Products of Acetylenedicarboxylic Acid Esters with Various Dinucleophiles. An application of C, H‐spin‐coupling constants

Abstract: SummaryHeterocyclic compounds obtained by addition of acetylenedicarboxylic acid esters to thioureas, cyclic amidines and o-difunctionalized aromatic systems have been studied by 13C-NMR. In particular, C, H-spin-coupling constants over two and three bonds were used to differentiate between the various constitutional isomers and to establish the configuration of trisubstituted exocyclic C, C-double bonds. The configurational significance and diagnostic value of vicinal cis and trans C, H-spin coupling is again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 22 publications
4
38
0
Order By: Relevance
“…With larger amounts of both isomers at hand, it is now possible to establish that there is a larger H-C(8), C(5')=0 heteronuclear coupling constant [5] in the ( E ) than in the ( Z ) isomer, and the same is true for aplysinopsin (l), as shown in Table 3. Another polar pigment isolated in only 1-mg amount from the Tubastraea sp., 6-bromo-3'-deimino-3'-oxoaplysinopsin (6), contains a Br-atom according to MS (Exper.…”
Section: Imino-l'l'-his(demethyl)-3'-oxoaplysinopsin (I) Andfor Thementioning
confidence: 78%
“…With larger amounts of both isomers at hand, it is now possible to establish that there is a larger H-C(8), C(5')=0 heteronuclear coupling constant [5] in the ( E ) than in the ( Z ) isomer, and the same is true for aplysinopsin (l), as shown in Table 3. Another polar pigment isolated in only 1-mg amount from the Tubastraea sp., 6-bromo-3'-deimino-3'-oxoaplysinopsin (6), contains a Br-atom according to MS (Exper.…”
Section: Imino-l'l'-his(demethyl)-3'-oxoaplysinopsin (I) Andfor Thementioning
confidence: 78%
“…In the literature it was reported that in reactions using unsubstituted imidazolidinediones and benzaldehydes or 3-substituted thiazolidinedione and 3-formyl chromone in an acidic medium, the main product was the Z isomer (15,18). The coupled 13 C NMR study of arylidene thiazolidinediones and imidazolidinediones also showed that only the Z isomer was formed (1,19). After the appropriate crystal of the compound 12 was obtained, Xray analysis was performed and the compound 12 (CCDC deposition number: CCDC-873382), was found to be Z isomer, as well ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature it was reported that in reactions using unsubstituted imidazolidinediones and benzaldehydes or 3-substituted thiazolidinedione and 3-formyl chromone in an acidic medium, the main product was the Z isomer 16,17 . The coupled 13 C NMR study of arylidene thiazolidinediones and imidazolidinediones also showed that only the Z isomer was formed 18,19 . In this study, only one isomer of the 172.14 ± 7.98 Plus DMSO (1 µg/mL) 100.5 ± 4.87 Plus DMSO (10 µg/mL) 94.12 ± 5.32 Note.…”
Section: Resultsmentioning
confidence: 99%